The Role of the Forum Komunikasi Umat Beragama in Building Religious Harmony in Banyumas Regency - Eka Safitri; Nur Wijayanti; Shofiyullah Shofiyullah (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2022)
This paper seeks to portray the life between religious communities in plural societies, namely in Banyumas Regency. The harmonious dynamics of life that are in line with the life philosophy are harmonious tentrem agawe santosa. Concerned pluralism in the community is built in the synergy between government apparatus, which in this case is strongly supported by KESBANGPOL in Banyumas Regency and as its driving force, the Banyumas Regency Religious Harmony Forum. This synergy is one of the basic foundations that can be used as a platform for activities that aim to communicate all religious people in Banyumas Regency. This type of research is qualitative research with research participation methods. The researcher collected data by interview, observation, and documentation. The results of this study state that Banyumas Regency is an area with a high diversity of religious diversity. The FKUB Communication Forum is one of the things that encourages harmony between religious people and is able to have a good sense of religious pluralism. In Banyumas Regency there are various faith-based community organizations and all of them are embraced in the Banyumas Regency FKUB. FKUB organizations are also made in every sub-district and with the emergence of organizations under the FKUB, the level of harmony in Banyumas Regency is getting better. The role and function of FKUB are increasingly clear in the community in an effort to maintain religious pluralism and counteract radicalism. The activities organized by FKUB are a way to gather people from various religions. Efforts to stir up the spirit of living harmoniously channeled through the written propaganda media, namely by using the BENER Bulletin (Beda Ning Rukun)